Obesity increases the risk of chronic pain development after motor vehicle collision. Issue 3 (March 2019) - Mauck, Matthew C.; Hu, JunMei; Sefton, Christopher; Swor, Robert A.; Peak, David A.; Jones, Jeffrey S.; Rathlev, Niels K.; Lee, David C.; Domeier, Robert M.; Hendry, Phyllis L.; McLean, Samuel A.
Abstract : Abstract: Obesity has been found to increase the risk of musculoskeletal pain (MSP) in other settings, but to our knowledge, the influence of increased body mass index on pain outcomes after common trauma exposures such as motor vehicle collision (MVC) has not been assessed. In addition, obesity results in biomechanical changes, as well as physiologic changes including reduced hypothalamic pituitary adrenal axis negative feedback inhibition, but mechanisms by which obesity may result in worse post-traumatic outcomes remain poorly understood. In this study, we evaluated the influence of body mass index on axial and overall MSP severity (0-10 numeric rating scale) 6 weeks, 6 months, and 1 year after MVC among 917 European Americans who presented to the emergency department for initial evaluation. After adjusting for an array of sociodemographic factors, obesity (particularly morbid obesity) was an independent risk factor for worse MSP after MVC (eg, RR 1.41 [95% CI 1.11, 1.80] for moderate or severe MSP 6 months after MVC among morbidly obese vs normal weight MVC survivors). Interestingly, substantial effect modification was observed between obesity risk and a genetic variant known to reduce hypothalamic pituitary adrenal axis negative feedback inhibition ( FKBP5 rs9380526). (eg, 41% vs 16% increased risk of moderate or severe MSP at 6 months among obese individuals with and without the risk allele.) Further studies are needed to elucidate mechanisms underlying chronic pain development in obese trauma survivors and to develop interventions that will reduce chronic pain severity among this common, at-risk group. Abstract : Supplemental Digital Content is Available in the Text.Prospective, longitudinal study shows that morbid obesity predicts greater chronic pain severity after motor vehicle collision.